2015
DOI: 10.1016/j.ejrh.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of natural waters and its relation to Buruli ulcer in Ghana

Abstract: a b s t r a c tStudy region: Buruli ulcer, an emerging disease caused by Mycobacterium ulcerans, largely affects poor rural populations in tropical countries. The environmental niche that supports this necrotizing bacterium is unclear. Here, water samples were collected from five communities within Ghana in the rainy season in 2011: four in the southern part of Ghana (three disease-endemic communities: Pokukrom, Betenase, and Ayanfuri, and one control: Kedadwen) and one non-endemic community (Nangruma) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In contrast to our study comparing water quality among M . ulcerans positive and negative sites, Hagarty et al (2015) compared water quality between three endemic and two non-endemic gold mining communities in Ghana [ 59 ]. They found that the study sites tended to be slightly acidic (pH < 7), whereas several sites assessed in our study recorded higher values of pH (pH < 8.7), especially in the Greater Accra region ( S2 Fig ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study comparing water quality among M . ulcerans positive and negative sites, Hagarty et al (2015) compared water quality between three endemic and two non-endemic gold mining communities in Ghana [ 59 ]. They found that the study sites tended to be slightly acidic (pH < 7), whereas several sites assessed in our study recorded higher values of pH (pH < 8.7), especially in the Greater Accra region ( S2 Fig ).…”
Section: Discussionmentioning
confidence: 99%